Conductivity and Local Structure of LaNiO3 Thin Films. Issue 18 (6th March 2017) - Fowlie, Jennifer; Gibert, Marta; Tieri, Giulio; Gloter, Alexandre; Íñiguez, Jorge; Filippetti, Alessio; Catalano, Sara; Gariglio, Stefano; Schober, Alexander; Guennou, Mael; Kreisel, Jens; Stéphan, Odile; et al.
Abstract : A marked conductivity enhancement is reported in 6–11 unit cell LaNiO3 thin films. A maximal conductivity is also observed in ab initio calculations for films of the same thickness. In agreement with results from state of the art scanning transmission electron microscopy, the calculations also reveal a differentiated film structure comprising characteristic surface, interior, and heterointerface structures. Based on this observation, a three‐element parallel conductor model is considered and leads to the conclusion that the conductivity enhancement for films of 6–11 unit cells, stems from the onset of intercompetition between the three local structures in the film depth. Abstract : A striking conductivity enhancement in 6–11 unit cell LaNiO3 thin films is speculated to stem from a playoff between three characteristic local structures in the film depth, which are seen by state of the art scanning transmission electron microscopy and further elucidated by first‐principles simulations.